Inter-level Spatial Cloud Compression Algorithm - Gupta, Pranab Kumar Das; Pattnaik, Sabyasachi; Nayak, Manojranjan (Defence Science Journal, 2014)
Static images of colour clouds play an important role to predict weather conditions to schedule proof and trial activities, and deploying resources at firing locations and observation posts. In this paper, a new inter-level cloud compression architecture and algorithm has been presented. Distributed architecture suitable for cloud computing has been suggested to implement inter-level compression algorithm (ILCA). Different possibilities between two successive cloud images have been combined to save the images of interest for further processing, ignoring the redundant ones. Vector quantisation technique is briefly discussed to achieve high level of compression. The algorithm presented in this paper can be easily modified to store flying, floating, and moving objects in air, water, and surface, respectively with high level of compression in various defence applications. Science Journal, Vol. 64, No. 6, November 2014, pp.536-541, DOI:http://dx.doi.org/10.14429/dsj.64.8115